Fabrication And Characterization Of Microcalcification Breast Phantom For Image Quality Analysis - Oyiwoja, Okoh Franca (2022)
This study aims to improve the early diagnosis of breast cancer through the application of image processing techniques based on the MATLAB algorithms to enhance the visibility of microcalcifications (MCs) in Full Field Digital Mammography (FFDM). Various polyvinyl alcohol (PVAL) composites phantoms were produced through freezing and thawing method to mimic the physical and radiological properties of different categories of breast tissue in line with the BIRADS classification. The density, elemental composition, effective atomic number (Zeff), electron density (ꝭeff), mass attenuation coefficients of the PVAL-based phantoms and MC features (CaCO3/graphite) were determined. The microstructure and CT number of the PVAL were also studied. The 50/50 water/ethanol-based 10 wt% PVAL (E50), the water-based 10 wt% PVAL (P10), 10 wt% PVAL mixed with 4% graphite powder (G4), and the heterogeneous phantom (H) had physical and radiological properties suitable to mimic BIRADS B, C, D, and a heterogeneous breast tissue respectively. Phantom E50, P10, G4, and H recorded densities of 0.952 ± 0.011 g/cm3, 1.056 ± 0.002 g/cm3, 1.081 ± 0.002 g/cm3, and 1.025 ± 0.006 g/cm3 respectively, their Zeff and ꝭeff ranged from 7.148 to 7.418 and 3.189 X 1023/cm3 to 3.209 X 1023/cm3 respectively.